2014
DOI: 10.1292/jvms.13-0103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pregnancy Status of Asian Elephants <i>(Elephas maximus)</i> by Measurement of Progestagen and Glucocorticoid and Their Metabolite Concentrations in Serum and Feces, Using Enzyme Immunoassay (EIA)

Abstract: The study was to find patterns of progestagen (progesterone and its metabolite) and glucocorticoid and their metabolite concentrations in serum and feces of pregnant Asian elephants (Elephas maximus). The 5 female Asian domestic elephants were naturally mated until pregnancy. After that, blood and feces samples were collected monthly during pregnancy for progestagen, glucocorticoid and their metabolites analysis by enzyme immunoassay (EIA). The results showed the serum progestagen concentration during gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…This study confirmed the presence of intrinsic cortisol patterns associated with reproductive state, ovarian cycle phase, and age in female Asian elephants, similar to that shown in other species and in previous studies of elephants [ 17 , 37 , 40 , 41 , 72 77 ]. Results further highlight the importance of accounting for these patterns when evaluating the impact of environmental factors on adrenal GC activity.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study confirmed the presence of intrinsic cortisol patterns associated with reproductive state, ovarian cycle phase, and age in female Asian elephants, similar to that shown in other species and in previous studies of elephants [ 17 , 37 , 40 , 41 , 72 77 ]. Results further highlight the importance of accounting for these patterns when evaluating the impact of environmental factors on adrenal GC activity.…”
Section: Discussionsupporting
confidence: 91%
“…Gobush et al . [ 25 ] found that fecal GC metabolites (fGCMs) increased with stage of gestation in free-ranging African elephants, while in Asian elephants, overall cortisol concentrations did not appear to be significantly altered during gestation, but increased sharply peripartum [ 40 , 41 , 83 ]. In examination of daily serum samples at the end of gestation, Meyer et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This ensures that the seasonal patterns captured reflect changes in the environment, rather than effects of growth or pregnancy; elephants in the young age category were still growing rapidly, and weight gain in pregnant females may be because of pregnancy rather than changes in condition. Pregnant females may also exhibit patterns of stress hormone changes associated with pregnancy ( Kajaysri and Nokkaew, 2014 ) rather than the seasonal variation in the environment we aim to study. Our aim is to focus on variation in markers of body condition and stress, rather than already pregnant ones.…”
Section: Methodsmentioning
confidence: 99%